Improved panels for clinical immune phenotyping: Utilization of the violet laser. Issue 5 (22nd May 2017) - Ryherd, Mark; Plassmeyer, Matthew; Alexander, Connor; Eugenio, Ines; Kleschenko, Yuliya; Badger, Ariel; Gupta, Raavi; Alpan, Oral; Sønder, Søren Ulrik
Abstract : Background: Clinical diagnostic laboratories are subject to numerous regulations imposed by government agencies. Laboratory developed tests for flow cytometry panels are essentially restricted to the use of analyte‐specific reagents (ASR) antibodies. With the advances in clinical flow cytometry systems, there is a trend toward the utilization of blue/red/violet laser flow systems and 8 to 10‐color panels. Currently, the selection of commercially available ASR antibodies for the violet laser is very limited. The market is dominated by Brilliant Violet 421 (BV421) manufactured by BD Biosciences and Pacific Blue (PB) manufactured by Beckman Coulter. In this study, we compare BV421 and PB conjugated ASR antibodies. Methods: Whole blood was stained and acquired on a Gallios flow cytometer system. For single color staining, the stain index (SI) was calculated. For the two panels, the compensation matrix was calculated and the performance of the antibody cocktails analyzed in FCS Express. Results: The results show that five out of six tested BV421 conjugated antibodies have significantly higher SI than their PB counterparts. Furthermore, BV421 antibodies require less compensation for spillover than PB. Finally, BV421 conjugated antibodies give better separation between negative and positive populations in the context of an 8 and 10 color panel without affecting the intensity of the other dyes. Conclusions: Overall, using BV421 conjugated antibodies results in better separation between populations compared to PB conjugated antibodies without negatively affecting other fluorochromes in our panels. We conclude that the BV421 conjugated ASR antibodies are currently the better available option for clinical flow panels. © 2017 International Clinical Cytometry Society